AMPK pathway is implicated in low level lead-induced pubertal testicular damage via disordered glycolysis. (March 2022) - Xie, Jie; Yu, Jun; Zhang, Zhaoyu; Liu, Duanya; Fan, Yongsheng; Wu, Yu; Ma, Haitao; Wang, Chunhong; Hong, Zhidan
Abstract: Lead (Pb) is a common environmental pollutant. It has been demonstrated that long-term exposure to Pb at environmental levels may cause severe and irreversible damage to the male reproductive system. Of note, the impairments may originate from environmental Pb exposure at puberty. However, the underlying mechanisms remain unclear. In this study, we administrated male ICR mice with 200 mg/L Pb through the drinking water for 30-, 60-, 90-day from postnatal day 28. RNA sequencing was performed in the control group and the 90-day Pb exposure group. It was found that Pb exposure induced testicular damage, increased oxidative stress levels and poor sperm quality. Bioinformatic analysis displayed 199 genes up-regulated (such as GLUT1 and MCT4 genes) and 156 genes down-regulated (such as GLUT3, PFK1, LDH, CD147 and AMPK genes) in the Pb exposure group compared to the control group. Gene ontology (GO) terms enrichment analysis showed differentially expressed genes (DEGs) are involved in the protein catabolic, cellular catabolic and triglyceride catabolic processes. KEGG pathways enrichment analysis indicated glycerolipid metabolism and AMPK signaling were significantly enriched. Furthermore, experimental verification showed that Pb exposure induces energy dysmetabolism and decreases glycolysis products in mice testicular tissue. The AMPK signaling pathway was found to be deactivated after Pb exposure. The GLUT1, GLUT3, PFK1 and LDH proteins, which play a critical role in the cell glycolysis process, also were decreased. Besides, the expression of CD147 was decreased and the location of CD147 was altered upon Pb exposure. Together, these findings indicated the implication of the AMPK signaling pathway in Pb exposure induced pubertal testicular damage and poor sperm quality by inhibiting cell glycolysis and disordering lactate transportation in testicular cells. Graphical abstract: Image 1 Highlights: Pubertal Pb exposure induces testicular injury and poor sperm quality. Pb exposure suppresses glycolysis and reduces lactate production in testes. Pb exposure disorders lactate transportation in testes. Inhibition of AMPK signaling pathway is involved in Pb exposure induced testicular injury.